Social reputation, psychosocial adjustment and adolescent peer victimization at the school context - Buelga, Sofía; Cava, María Jesús; Musitu, Gonzalo (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study was to analyse the relationship among adolescent’s social reputation –perceived and ideal-, peer victimization at the school context and some specific psychosocial adjustment variables such as life satisfaction, loneliness, depressive symptomatology and self- esteem. The sample was composed of 1319 adolescents aged from 11 to 16 years old. Structural equation modeling was carried out to examine the direct and indirect effect of social reputation on peer victimization. Results obtained indicated social reputation was related both directly and indirectly to peer victimization. The indirect effects suggested self-esteem, depressive symptomatology and loneliness mediated the relationship between the adolescent’s social reputation and peer victimization. Finally, these results and their implications were discussed.